Identification of filamentous Fungi Isolated from Clinical Specimens by MALDITOF Mass Spectrometry in A Tertiary Health Care Centre - Butta, Hena; Sardana, Raman; Grover, Ashmita; Mendiratta, Leena; Kansal, Sudha; Goyal, Neerav (Annals of Pathology and Laboratory Medicine, 2019)
Background: Matrix Assisted Laser Desorption Ionisation- Time of Flight Mass Spectrometry (MALDI-TOF MS) has revolutionized the identification of microorganisms particularly bacteria and yeasts in terms of rapidity, cost-effectiveness, automation and enhanced discriminatory power. Its utility for the identification of filamentous fungi lags due to certain challenges like effective protein extraction method and limited databases. The conventional methods for the identification of filamentous fungi are time consuming and may not establish the definitive species identification. Keeping this in mind, we planned this study to evaluate MALDI-TOF Vitek MS (Biomerieux, France) for the identification of filamentous fungi, to standardize the mould identification protocol and to correlate the identification results by MALDI TOF MS with the conventional phenotypic methods. Methods: The identification of clinically significant filamentous fungi isolated from various clinical specimens was done by both conventional method and MALDITOF Vitek MS using Ethanol-Formic acid –Acetonitrile protocol. The unidentified fungi by both the methods were identified in the reference Mycology laboratory. Result: Out of 50 clinically significant moulds isolated from various clinical specimens during study period, 35 (70%) could be identified using MALDI-TOF Vitek MS and all the identification results corroborated with the phenotypic method for identification with no misidentification. In addition to Aspergillus species, the identification of Zygomycetes and Phaeoid fungi could also be possible using MALDI TOF Vitek MS. Conclusion: MALDITOF MS was found to be a rapid and reliable method for the species identification of filamentous fungi. We could standardize two extraction protocols using Ethanol-Formic acid -Acetonitrile at our institute for the identification of filamentous fungi by MALDI TOF Vitek MS. We also emphasize on the creation of own in-house library for the optimum utilization of MALDI TOF Vitek MS for the identification of filamentous fungi.